Nematic Ordering of Anisotropic Nanoparticles in Block Copolymers. Issue 1 (8th December 2021) - Diaz, Javier; Pinna, Marco; Zvelindovsky, Andrei V.; Pagonabarraga, Ignacio
Abstract: Block copolymer melts have been previously used to control the position and alignment of anisotropic nanoparticles. In this work, 2D and 3D mesoscopic simulations are used to explore the phase behavior of block copolymer/nanoparticle systems. The method combines a time‐dependent Ginzburg‐Landau for the polymer and Brownian dynamics for the anisotropic nanoparticles. Rhomboidal and spheroidal shaped particles are simulated in two and three dimensions, respectively. It is found that the nanoparticle nematic order aligned by the block copolymer domains enhances the lamellar phase of the block copolymer, due to an anisotropy‐driven phase transition. Additionally, anisotropic nanoparticles within circular‐forming block copolymer leads to a competition between the nematic colloidal ordering and the hexagonally ordered mesophase. At large concentrations, the nematic order dominates, deforming the block copolymer mesophase. Abstract : Block copolymer melts can be used to control the alignment of anisotropic nanoparticles. Moreover, the nanoparticle anisotropy is found to modify the block copolymer structure promoting elongated domains when miscible with the minority phase, or co‐assemble into nematically ordered dense regions, when miscible with the majority phase of the block copolymer. The competition between the nanoparticle nematic order and the block copolymer mesophase leads to complex co‐assembled phase behavior.